The school culture - Brunetti, Immacolata (Formazione & insegnamento, 2017)
This paper aims at provide a definition of teacher’s values at international level by explaining the different facets created over time. Thus the value of the feature as an umbrella term to denote not only guiding ideas of our behavior and our choices but also assessments of situations. It is very necessary to study on teachers’ values in order to understand all the professional context in which teachers operate as they make their own of the school’s culture in which they work. The results show that the environment affects their values and is unaffected (Dewey, 1968) and each one make sense and meaning to the experience on the basis of their values.